Correlation of Otorhinolaryngologic Symptoms with Physical Findings in Behcet-s Disease - DOĞAN, REMZI; MERIC, A.; SU KÜÇÜK, ÖZLEM; SU, O.; EREN, SABRİ BAKİ; DOGAN, REMZİ; TUĞRUL, SELAHATTİN; EREN, S. B.; ÖZTURAN, ORHAN; TUGRUL, SELHATTİN; Ozturan, ORHAN (My University, 2015)
Objective: Behcet-s disease is a chronic systemic inflammatory disease of unknown etiology. We examined the correlation between otorhinolaryngologic symptoms and otorhinolaryngologic physical findings in patients with Behcet-s disease, in search of strategies to reduce the morbidity rates.